Low health-related quality of life in school-aged children in Tonga, a lower-middle income country in the South Pacific - Solveig Petersen; Boyd Swinburn; Helen Mavoa; Kalesita Fotu; Caroline Tupoulahi-Fusimalohi; Gavin Faeamani; Marjory Moodie (Taylor & Francis Group, 2014)
Background: Ensuring a good life for all parts of the population, including children, is high on the public health agenda in most countries around the world. Information about children's perception of their health-related quality of life (HRQoL) and its socio-demographic distribution is, however, limited and almost exclusively reliant on data from Western higher income countries. Objectives: To investigate HRQoL in schoolchildren in Tonga, a lower income South Pacific Island country, and to compare this to HRQoL of children in other countries, including Tongan children living in New Zealand, a high-income country in the same region. Design: A cross-sectional study from Tonga addressing all secondary schoolchildren (11-18 years old) on the outer island of Vava'u and in three districts of the main island of Tongatapu (2,164 participants). A comparison group drawn from the literature comprised children in 18 higher income and one lower income country (Fiji). A specific New Zealand comparison group involved all children of Tongan descendent at six South Auckland secondary schools (830 participants). HRQoL was assessed by the self-report Pediatric Quality of Life Inventory 4.0. Results: HRQoL in Tonga was overall similar in girls and boys, but somewhat lower in children below 15 years of age. The children in Tonga experienced lower HRQoL than the children in all of the 19 comparison countries, with a large difference between children in Tonga and the higher income countries (Cohen's d 1.0) and a small difference between Tonga and the lower income country Fiji (Cohen's d 0.3). The children in Tonga also experienced lower HRQoL than Tongan children living in New Zealand (Cohen's d 0.6). Conclusion: The results reveal worrisome low HRQoL in children in Tonga and point towards a potential general pattern of low HRQoL in children living in lower income countries, or, alternatively, in the South Pacific Island countries.